2021
DOI: 10.1111/bph.15622
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor exerts pro‐proliferative and anti‐apoptotic effects via CD74 in murine hepatocellular carcinoma

Abstract: The data that support the findings of this study are available from the corresponding author upon reasonable request. Some data may not be made available because of privacy or ethical reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…The receptor gene CD74 may participate in the regulation of antigen presentation for immune response. The interaction of MIF and CD74 was reported to exert proproliferative and antiapoptotic effects in murine hepatocellular carcinoma [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The receptor gene CD74 may participate in the regulation of antigen presentation for immune response. The interaction of MIF and CD74 was reported to exert proproliferative and antiapoptotic effects in murine hepatocellular carcinoma [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Blocking MIF-CD74 signalling not only inhibits the proliferation of HCC cells but also exerts antitumour effects. Therefore, MIF/CD74 axis inhibition could be an effective treatment for HCC ( 28 ). SPP1 encodes osteopontin (OPN), a phosphorylated glycoprotein expressed in various tissues and cells associated with human diseases ( 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…MIF has been confirmed to contribute to a variety of facets of tumor growth, including cell proliferation, differentiation, and angiogenesis. MIF can bind to its receptor CD74 in the TME, which is present on TAMs, DCs, Treg cells, and MDSCs, facilitating immunological escape and cancer growth ( 63 , 64 ). For the first time, our study found that MIF may inhibit memory B-cell activity in HCC and that inhibiting the MIF-CD74 axis may be a new treatment strategy.…”
Section: Resultsmentioning
confidence: 99%